Weighing Delight and Dole in Canadian Poetry - Nela Bureu Ramos (Miscelánea: A Journal of English and American Studies)
The analysis of the relationship between man and nature in Canadian poetry  written in English shows that Canadian artists have traditionally been both  attracted and repelled by the vastness and savage beauty of the Canadian  landscape and, consequently, have described their land as both heaven and  hell, a matrix of life and a source of terror and death.